2011
DOI: 10.1017/s1742170511000196
|View full text |Cite
|
Sign up to set email alerts
|

Mapping potential foodsheds in New York State by food group: An approach for prioritizing which foods to grow locally

Abstract: Public interest in local food continues to grow, but few analyses have examined the capacity for the US population to be supplied through local and regional food systems. This paper extends earlier work that demonstrated a method for mapping potential foodsheds and estimating the potential for New York to meet the food needs of the state's population centers. It provides a methodology for addressing the question, 'If land is limited, which foods should be grown locally?' A spatial model was developed to alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…Even at the local scale, however, there are ongoing questions and knowledge gaps over issues such as the ability of farms to sustain local populations with the quantity and variety of necessary food and the energy efficiencies of local‐scale food systems (Clancy and Ruhf, 2010; Martinez et al, 2010). As a result, there is increased interest in the study of regional‐scale food production systems as a balance between local and global food systems (Stevenson et al, 2011; Peters et al, 2012). While local systems typically encompass 80‐ to 160‐km radii, regional systems are defined by boundaries large enough to include multiple states (Clancy and Ruhf, 2010) and thus have the potential to offer greater food production capacity, efficiency, and security.…”
mentioning
confidence: 99%
“…Even at the local scale, however, there are ongoing questions and knowledge gaps over issues such as the ability of farms to sustain local populations with the quantity and variety of necessary food and the energy efficiencies of local‐scale food systems (Clancy and Ruhf, 2010; Martinez et al, 2010). As a result, there is increased interest in the study of regional‐scale food production systems as a balance between local and global food systems (Stevenson et al, 2011; Peters et al, 2012). While local systems typically encompass 80‐ to 160‐km radii, regional systems are defined by boundaries large enough to include multiple states (Clancy and Ruhf, 2010) and thus have the potential to offer greater food production capacity, efficiency, and security.…”
mentioning
confidence: 99%
“…On the production side, we see potential for further research identifying land area suitable for growing a sufficient amount of crops, ensuring sustainable production methods. Next steps could also go beyond our assumption that the current mix of crop production would not change to identify what additional varieties of crops are possible to grow in the country, and how diverse the local food production might become as a result, perhaps using the methods of Peters et al (2011) to prioritize which food groups to grow locally, using spatial modeling of potential foodsheds. With work already underway towards mapping land use in Iceland (Agricultural University of Iceland 2008), there is potential to match these data with the amount of land area needed to grow the main crops, according to the most suitable soil type and weather conditions in each area of the country.…”
Section: Discussionmentioning
confidence: 99%
“…They found that reductions in greenhouse gas emissions are gained from an appropriate choice of local crops that can substitute for foods with high carbon footprints. Such crop prioritizing for sustainability also can be applied to broader multi-foodshed areas, as has been done for New York State [57].…”
Section: Ecological Sustainabilitymentioning
confidence: 99%